2021
DOI: 10.24931/2413-9432-2021-10-2-34-41
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of acute pain syndrome after septoplasty

Abstract: The paper evaluates the effectiveness of the use of therapeutic laser exposure (photobiomodulation therapy – PBMT) to minimize acute pain in the early postoperative period in patients after septoplasty. The study included two groups of patients. Patients of the first group (31 patients) underwent septoplasty with standard management in the postoperative period. Patients of the second group (31 patients) also underwent septoplasty, and then added PBMT to the standard measures of the postoperative period at 3, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Due to the toxicity and other potential undesirable effects of pharmacological agents, the search for non-drug methods to combat pain has now been updated. Thus, photobiomodulation (PBM) using low-intensity laser radiation (LILR) is used in clinical practice to reduce patients' level of pain [4][5][6]. Experimental work of domestic and foreign researchers (in vitro and in vivo) has shown that the effect of FBM is due to a multi-link chain of consequences from the primary absorption of photons by biological tissues [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the toxicity and other potential undesirable effects of pharmacological agents, the search for non-drug methods to combat pain has now been updated. Thus, photobiomodulation (PBM) using low-intensity laser radiation (LILR) is used in clinical practice to reduce patients' level of pain [4][5][6]. Experimental work of domestic and foreign researchers (in vitro and in vivo) has shown that the effect of FBM is due to a multi-link chain of consequences from the primary absorption of photons by biological tissues [7][8][9].…”
Section: Introductionmentioning
confidence: 99%